Requirement of digestible methionine + cystine in Japanese quails during the laying phase - Rodrigues, Taynara Prestes Perine Moretto (2023)
An experiment was carried out with Japanese quails in the initial laying phase, from 43 to 168 days of age, to determine the nutritional requirement of digestible methionine + cystine for this period. 375 quails were used, being fifteen quails used per experimental unit. A total of 5 treatments (0.60, 0.75, 0.90, 1.05 and 1.20% digestible methionine + cystine) were used in a completely randomized design with 5 replicates each. The performance parameters evaluated were feed intake (g / bird), body weight (g), egg weight (g), laying rate (%), egg mass (g eggs.bird.day-1), feed conversion by mass and dozen eggs (g.g-1 of eggs, g.dz-1 of eggs), viability (%) and the body chemical composition (%). The egg quality parameters were: % of component (yolk, albumen and shell relative to egg weight), specific gravity (g mL-1), Haugh unit, yolk index, shell weight per surface area and thickness of the shell (mm). Quadratic effect was found on the performance parameters evaluated (P<0.05), except for age at first egg and viability with linear effect. Regarding egg quality, no significant effect was observed on the variables tested (P>0.05). The nutritional recommendation of digestible methionine + cystine for Japanese quails at laying phase is 0.90% from the maximum point obtained for the egg mass, egg weight and laying rate, corresponding to daily intake of 241.54 mg of digestible methionine + cystine / day, respectively.Keywords: body composition; egg mass; egg quality; egg weight.